DISPARITAS PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA KEKERASAN TERHADAP PEREMPUAN - Ridho Mubarak (Universitas Medan Area, 2015)
In public service activities and service development, developing countriesoften encounter resistance, and resistance was due to the limitations,capabilities and complexity of the bureaucratic apparatus. In overcomingthese problems, one of them is structural reform. The implementation ofstructural reforms is to realize the regional autonomy. The implications ofregional autonomy, local governments and/or city government must havethe entrepreneurship spirit which is able to provide the best possibleservice to the community. In this context, the city government and/orlocal governments should be able to reconcile the needs of the communitywith the products. Thus, in implementing the policy of regional autonomy will be success efficiently, more productively, simply, and timely.